2023
DOI: 10.1007/s00109-023-02342-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of mutational variants in beta and alpha genes in patients with hemoglobinopathies from two large Greek centers: a complex interplay between genotype and phenotype

Michael D. Diamantidis,
Rebecca-Anastasia Karanikola,
Chrysoula Polyzoudi
et al.

Abstract: Hemoglobinopathies affect patients in the wider Mediterranean area and consist of 4 distinct subgroups: beta thalassemia major (TM), beta thalassemia intermedia (TI), sickle cell disease syndromes (SCD) (homozygous SCD, SCD/beta thalassemia trait) and hemoglobinopathy H (alpha thalassemia). The clinical spectrum of these syndromes varies from mild to severe. Complex interactions between genes and environmental factors form the clinical manifestations in hemoglobinopathies. There is an unmet need to clarify the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In patients with β-thalassemia, co-inheritance of α-globin gene variants, leading to absence or reduction of α-globin synthesis, were associated with a milder clinical course. 18 In our cohort, ELS was significantly higher in patients with Mix and significantly higher than that in patients with TI, which further confirmed that co-inheritance of α-thalassemia alleviated hemolysis in patients with β-thalassemia. However, the CO concentration and ELS in patients with Mix were more similar to those in patients with TM.…”
Section: Discussionsupporting
confidence: 83%
“…In patients with β-thalassemia, co-inheritance of α-globin gene variants, leading to absence or reduction of α-globin synthesis, were associated with a milder clinical course. 18 In our cohort, ELS was significantly higher in patients with Mix and significantly higher than that in patients with TI, which further confirmed that co-inheritance of α-thalassemia alleviated hemolysis in patients with β-thalassemia. However, the CO concentration and ELS in patients with Mix were more similar to those in patients with TM.…”
Section: Discussionsupporting
confidence: 83%
“…They concluded that co‐inheritance of α−3.7 among 15 TM increased haemoglobin level reduced severity whereas double heterozygotes with α‐triplication and TI presented with a more severe phenotype. However, no frequency or rate was mentioned in the study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] found α‐triplication in three β thal patients having β 0 /β + or β ++ and 26 β thal carriers but having severe clinical presentation out of 181 patients studied, whereas Farashi et al. [ 19 ] found α‐triplication in 14 β thal carriers and 9 β‐thal major out of 1700 patients studied. None of them commented on the influence of α‐triplication on disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation